NEW POTENTIAL AND PROSPECTS OF THE ECONOMY AND SOCIAL SPHERE DEVELOPMENT OF YAKUTIA - Afanasievich, Popov Anatoliy; Nikolaevich, Myreev Anatoliy; S.V., Fedorova; Vladislavovna, Sergeeva Valentina (The journal of contemporary issues in business and government, 2021)
North regions have severe conditions but they also have and advantages like small populations and large territories without human intervention. The current research is dedicated to the perspectives and potential of the developing and resolving social and economic issues of the Republic of Sakha (Yakutia). In this article was analyzed citizens' incomes and the life-rate of economic active socials in the republic. It is fact, the innovations in the different branches of the regional economy will help to achieve positive changes in the republic economy and especially in its social brunch. It is too important for the republic of Sakha to resolve the problem of the connection with the region's compounds, and other Russian federal parts. In accelerating the development of the economy and social sphere, the main role will be played by rational employment, efficient use of the able-bodied population, and the support of the young generation. Tourism and recreation business can become key to resolve the economic and social problems of the region.